Effect of sodium oxide molar ratio on bentonite supported catalyst for the transestrification of waste cooking oil / Izyan Yusof - Yusof, Izyan (2024)
Presently, in addition to the feedstock and solvent, very expensive catalyst materials are used in the production of biodiesel. The aim of this study is to convert waste cooking oil (WCO) into biodiesel via transesterification with Na2O/bentonite catalyst. Six series of modified Na2O/bentonite were prepared at different NaOH-bentonite molar ratio (1:1, 2:1, 3:1, 4:1, 5:1, and 6:1) via wet impregnation method. The synthesized catalyst was successfully characterized using CO2-Temperature Program Desorption (CO2-TPD), BET surface analysis, Powder X-Ray Diffraction (PXRD), Field Emission Scanning Microscopy with Energy Dispersive X-Ray Spectroscopy (FESEM-EDX), Thermogravimetric Analysis (TGA), and Fourier Transform Infrared Spectroscopy (FTIR). The WCO feedstock had undergo pretreatment analysis to fit the transesterification process. The screening test of the Na2O/bentonite catalysts was conducted via transesterification reaction and optimized using Response Surface Method (RSM) with Box-Bechken Design (BBD). In addition to the reusability test and spent catalyst analysis, the heterogeneous Na2O/bentonite catalyst's catalytic activity was evaluated. The crystallinity of the synthesized catalyst proved to be a semi-cryatalline materials via PXRD analysis. Successful impregnation of Na2O compound into bentonite was highly proved as the important peak, Na2O appeared at 2θ = 26.581, 35.693, 39.501, 43.275, and 53.883°. CO2-TPD analysis results indicate that Na2O/bentonite catalyst have strong and very strong basic site based on the temperature desorption. In general, the total basicity increases when the molar ratio of Na2O increase. The decreasing surface area from 57.44 m2/g (raw bentonite) to 2.675.56 m2/g (Na2O/bentonite catalysts) indicated successful impregnation of Na2O molecules into the bentonite’s porous structure. The WCO pretreatment shows that the free fatty acids (FFA) value, saponification value, and average molecular weight are 0.99 wt%, 156.21 mg KOH/g, and 1090.51 g/mol, respectively. The screening test of Na2O/bentonite catalysts shows that 5:1 molar ratio found to be the best ratio with FAME yield of 85.4%. ANOVA analysis shows that a quadratic polynomial model had been developed with R2=0.9583, and insignificant lack-of-fit. By using RSM, 55.81% (residual standard error, RSE: 2.74%) of FAME yield was achieved at the optimum reaction condition of 17.9:1 methanol-to-oil molar ratio, reaction temperature of 50.6 °C for 11.9 hours, with 4.7 wt% of a 5:1 Na2O/bentonite catalyst loading. The catalyst reusability test found that the catalyst can be used up to three cycles. The CO2-TPD shows that the catalyst starts to degenerate at 4th cycle as the total basicity drops from 913.30 to 509.70 μmol CO2/g. The leaching process had caused the increase in BET surface area (2.9734 to 3.4420 m2/g) after the 6th cycle due to the sodium moving out from the bentonite’s and decrease of sodium atomic percentage from 6.03 % to 3.56 % from the FESEM-EDX analysis. For recommendation, alternative support catalysts like graphitic carbon nitride can improve catalyst stability and reduce sodium leaching as one study success to produced over 90% biodiesel in ten cycles.